Penerapan Teknologi Mesin Bordir Otomatis Sebagai Daya Saing Usaha Konveksi Bordir Indah Collection - Handika Bayu Alfarris; Koerniawan Hidayat (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The implementation of automatic embroidery machines is an alternative that can increase the effectiveness and efficiency of the production process carried out by the Indah Collection Embroidery Convection. In practice, it discusses the application of automatic embroidery machine technology and the competitiveness of the Indah Embroidery Convection business. The method in this paper is based on a video that discusses the application of machine embroidery technology. The application of an automatic embroidery machine is divided into several stages: the initial stage, the production stage, the finishing stage. The results of the discussion found that the application of automatic embroidery machine technology is more widely used than manual embroidery machines and raises the competitiveness of embroidery convection businesses using both automatic and manual embroidery machines.